2020
DOI: 10.3389/fpubh.2020.00095
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Antimicrobial Resistance of Haemophilus influenzae in Adult Patients in Shanghai, China

Abstract: Background: The serotype and antimicrobial resistance of Haemophilus influenzae in adult patients have changed due to the application of antimicrobials and H. influenzae type b (Hib) vaccine worldwide. However, the epidemiologic characteristics of H. influenzae in Shanghai are still unavailable. Objective: To determine the serotype distribution, antimicrobial resistance and multilocus sequence type (MLST) of H. influenzae in adult patients in Shanghai. Methods: A total of 51 clinical isolates from adult patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
(36 reference statements)
2
14
0
Order By: Relevance
“…Moreover, MIC variance increases through time, first with a decreasing and then an increasing mean MIC (Supplementary Fig. 13) whereby the frequency of resistance in ATLAS is broadly consistent with other recent reports 61 .…”
Section: Resultssupporting
confidence: 90%
“…Moreover, MIC variance increases through time, first with a decreasing and then an increasing mean MIC (Supplementary Fig. 13) whereby the frequency of resistance in ATLAS is broadly consistent with other recent reports 61 .…”
Section: Resultssupporting
confidence: 90%
“…However, in our study, 18 isolates of BLNAR were identified from 196 test isolates (9.2%). A former report in Shanghai, China, and Beijing, China, the detection rate of BLNAR strains was 11.76 and 18.9% (24,25). In other countries, especially, Japan, BLNAR strains prevalence was >40% (3).…”
Section: Discussionmentioning
confidence: 90%
“…Over one-third (34.4%) of the β-lactamase producer isolates were resistant to trimethoprim-sulfamethoxazole and mutations associated with this resistance phenotype were detected in folA and folP of three isolates analyzed by WGS [ 80 ]. High rates of resistance to trimethoprim-sulfamethoxazole were observed in previous studies [ 27 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 60%